2009
DOI: 10.1186/1753-4631-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed functional brain networks and neurocognitive function in low-grade glioma patients: a graph theoretical analysis of resting-state MEG

Abstract: Background: To understand neurophysiological mechanisms underlying cognitive dysfunction in low-grade glioma (LGG) patients by evaluating the spatial structure of 'resting-state' brain networks with graph theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
118
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 41 publications
12
118
2
3
Order By: Relevance
“…Network theory has been used to examine functional and structural brain connectivity over the past several years (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Examination of MEG data using these techniques has demonstrated that functional brain network organization is a biologically meaningful phenotype being altered in disease states (25) in ways that can be linked to behavioral task performance (60)(61)(62). Moreover, network organization demonstrates temporal variability that can be induced by cognitive remediation strategies (63), task practice (64), learning (41,53,65), or task difficulty (66).…”
Section: Discussionmentioning
confidence: 99%
“…Network theory has been used to examine functional and structural brain connectivity over the past several years (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Examination of MEG data using these techniques has demonstrated that functional brain network organization is a biologically meaningful phenotype being altered in disease states (25) in ways that can be linked to behavioral task performance (60)(61)(62). Moreover, network organization demonstrates temporal variability that can be induced by cognitive remediation strategies (63), task practice (64), learning (41,53,65), or task difficulty (66).…”
Section: Discussionmentioning
confidence: 99%
“…Network randomization has mainly been found in higher frequency bands (Bartolomei et al, 2006b; Bosma et al, 2009). In lower frequency bands, brain tumors may give rise to abnormal increase in clustering (Bosma et al, 2009). Of interest, the latter observation corresponds to the increase in the normalized clustering coefficient observed after lesions in our model.…”
Section: Discussionmentioning
confidence: 97%
“…These differences in network structure may be directly related to symptoms of PTSD. Reductions in network efficiency have been related to poorer cognitive performance, particularly in areas of processing speed, learning, and memory (Bosma et al, 2009;Douw et al, 2011;Geib et al, 2015;Schedlbauer et al, 2014). Deficits in attention, learning, and memory have previously been demonstrated in individuals with PTSD .…”
Section: Discussionmentioning
confidence: 99%